JURIDICAL REVIEW OF LEGAL PROTECTION AGAINST COMMUNITIES IN INDONESIA WHO ARE ENTANGLED IN THE ILLEGAL LOAN PERFORMANCE SYSTEMATIC FROM THE FIQH SIYASAH PERSPECTIVE - Humaidi Fathani; Yusriyah Darma Sitanggang; Zhenyu Cui (PT. Radja Intercontinental Publishing, 2023)
This paper aims to determine the status of legal protection for people who are caught in the systematic performance of illegal loans, reviewed juridically and from the legal perspective of siyasah dusturiyah. This writing is motivated by the various problems currently being faced by the community who are fearful of feeling anxious due to the impact of the performance of illegal loans which are considered to be arbitrarily acting and taking away someone's freedom in an unusual way, so this must be explored further in solving these problems. The research method used is the Normative Juridical method with a descriptive analysis approach. The results of this research show that the systematic performance of pinjol in Indonesia is contradictory and contrary to the legal norms or regulations in force. Because lending is the same as an act of extortion and a violation of the ITE Law, seen from the aspect of violating the ITE Law, if a fine limit is not respected, users of illegal lending services will suffer consequences in the form of commercial distribution of all data or biodata contained in the resident's identity and ultimately data leakage occurs. According to the legal perspective of siyasah, this loan problem is essentially a problem related to social norms or siyasah dusturiyah, a policy from the government which opens up opportunities in the implementation of the OJK (Financial Services Authority) and does not rule out the possibility of also opening up opportunities for the implementation of illegal loans. In terms of fiqh, this problem is included in the issue of siyasah dusturiyah which violates the principles of a policy in Islamic law.